A modified polyvinylchloride surface with antibacterial and antifouling functions. (4th February 2019) - Almousa, Rashed; Wen, Xin; Na, Sungsoo; Anderson, Gregory; Xie, Dong
Abstract : Surfaces with antibacterial and hydrophilic properties are very attractive to cardiovascular applications. The objective of this study was to synthesize and immobilize a novel antibacterial and hydrophilic polymer onto surface of polyvinylchloride via an effective and mild surface coating technique. The surface coated with a terpolymer constructed with N ‐vinylpyrrolidone, 3, 4‐dichloro‐5‐hydroxy‐2(5 H )‐furanone derivative, and succinimide residue was evaluated with cell adhesion, bacterial adhesion, and bacterial viability. 3T3 mouse fibroblast cells and two bacteria species were used to evaluate surface adhesion and antibacterial activity. Results showed that the polymer‐modified polyvinylchloride surface exhibited not only significantly decreased 3T3 fibroblast cell adhesion with a 66% to 87% reduction but also significantly decreased bacterial adhesion with 69% to 87% and 52% to 74% reduction of Pseudomonas aeruginosa and Staphylococcus aureus attachment, respectively, as compared with original polyvinylchloride. Furthermore, the modified polyvinylchloride surfaces exhibited significant antibacterial functions by inhibiting bacterial growth (75%‐84% and 78–94% inhibition of P aeruginosa and S aureus, respectively, as compared to original polyvinylchloride) and killing bacteria. These results demonstrate that covalent polymer attachment conferred antifouling and antibacterial properties to the polyvinylchloride surface.